Catalytic oxidation of alkanes by iron bispidine complexes and dioxygen: oxygen activation versus autoxidation - Comba, Peter; Lee, Yong-Min; Nam, Wonwoo; Waleska, Arkadius (Chemical communications, 2014)
Organic substrates (specifically cis-1,2-dimethylcyclohexane, DMCH) are oxidized by O2 in the presence of iron(II)-bispidine complexes. It is shown that this oxidation reaction is not based on O2 activation by the nonheme iron catalysts as in Nature but due to a radical-based initiation, followed by a radical- and ferryl-based catalytic reaction.